Mekanisme Penyelesaian Pembiayaan Macet pada Baitul Qiradh Baiturrahman Banda Aceh - IB, Bukhari; Mustamim, Mustamim; Majid, Jamaluddin (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
The non-performing financing that occurred at the Baitul Qiradh Baiturrahman Banda Aceh Sharia Cooperative in 2021 reached IDR 332,312,000, - involving 70 financing members. One of the main causes of non-performing financing is the failure of members' businesses caused by errors in assessing business prospects and other factors. To overcome this problem, an appropriate resolution mechanism is needed. As an institution that operates on sharia principles, the mechanism for resolving non-performing financing must also consider sharia values. This study aims to determine the mechanism for resolving non-performing financing applied at the Baitul Qiradh Baiturrahman Banda Aceh Sharia Cooperative. This study uses a qualitative approach with descriptive analysis. Data were collected through interviews, observations, and documentation. The results of the study indicate that the Baitul Qiradh Baiturrahman Banda Aceh Sharia Cooperative implements restructuring mechanisms such as rescheduling and reconditioning, as well as other resolution options such as arbitration and litigation.